2009
DOI: 10.2355/isijinternational.49.1316
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Optimization of Ironmaking with Biomass as Auxiliary Reductant in the Blast Furnace

Abstract: The potential of using biomass in ironmaking is investigated by simulation. Biomass is used to partially replace fossil reductants in the blast furnace process, which is described mathematically by a thermodynamic model. The model is cast in linear form to facilitate an efficient economic optimization of the production of raw steel, considering costs of raw materials, energy and CO 2 emissions of the unit processes up to the basic oxygen furnace. The high oxygen content and low heating value of biomass makes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 8 publications
3
34
0
Order By: Relevance
“…Intensive work is being done to mitigate the CO 2 emissions in steel industry by partial substitution of fossil fuels (coal and coke) with renewable source of energy such as biomass. [7][8][9][10][11][12][13][14][15] One of biomass materials which could be used as binder for briquettes and reducing agent in blast furnace is lignin. Lignin is considered as the second most abundant renewable biomass on the earth after cellulose and it represents about 30% of the total raw biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive work is being done to mitigate the CO 2 emissions in steel industry by partial substitution of fossil fuels (coal and coke) with renewable source of energy such as biomass. [7][8][9][10][11][12][13][14][15] One of biomass materials which could be used as binder for briquettes and reducing agent in blast furnace is lignin. Lignin is considered as the second most abundant renewable biomass on the earth after cellulose and it represents about 30% of the total raw biomass.…”
Section: Introductionmentioning
confidence: 99%
“…5) As expected, the costs of CO 2 emissions and stripping/storage were found to affect the optimal degree (b) of top gas recycling, with lower values of b at higher stripping cost, and maximum recycling at higher costs of emissions. In the following, some examples have been chosen to illustrate the optimal states of the system, with the emission and stripping/storage costs reported in Table 3.…”
Section: Resultsmentioning
confidence: 71%
“…We study the units in an integrated steel works from the raw material processing units through one blast furnace to the basic oxygen furnace (BOF), 5) with liquid steel as the main product (Fig. 1).…”
Section: The Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…(Helle et al, 2010;Helle et al, 2009;Gupta, 2003;Suopajärvi and Fabritius, 2012; . Helle et al (2010) and Helle et al (2009) simulated partial substitution of fossil reducing agents with biomass in the BF. They concluded that the biomass had to be pre-processed through pyrolysis, because the high oxygen content and low heating value of raw biomass would reduce the productivity of the BF.…”
Section: Biomass As Reducing Agent and Fuelmentioning
confidence: 99%